I have trouble showing that `((p ∨ q) → r) → (p → (q ∨ r))`

it is valid by means of a semantic table.

I know it's valid because I was able to test it using the following truth table:

As far as I know, a semantic table is a test of satisfaction. And a formula is valid if its denial is unsatisfactory. Therefore, I will need to construct a semantic table using formula negation and demonstrate that formula negation is unsatisfactory, making the formula valid.

So this was my attempt to build a semantic box for the formula:

My problem is that there is only one closed branch for this semantic box that I have built. And as far as I know, all branches must be closed so that this negation formula is not valid.

Any idea where I've strayed?